Pemberdayaan Masyarakat dalam Meningkatkan Pemasaran Melalui Digital Marketing UMKM Kelurahan Keputih Surabaya - Irma Nur Hanifa; Dhani Ichasanuddin Nur (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
MSMEs play a very important role for the progress of the Indonesian economy. With the involvement of MSMEs as a driver of improving the economy in Indonesia, it is certainly hoped that MSMEs can continue to develop in the long term. In the current era, MSME actors are expected to be able to make the best use of technology. One of them is the world of digital marketing, because digital marketing has an extraordinary influence so that MSMEs can continue to develop in the long term. This prompted the East Java MBKM Thematic KKN UPN Veterans Group 74 to hold counseling with the theme "Utilization of Digital Marketing in Improving MSME Marketing" this is also because the results of surveys and observations that have been conducted by KKN-T MBKM Group 74 Surabaya showed a lack of knowledge and the use of digital technology in marketing. Therefore, by holding this counseling, it is hoped that MSME actors can develop more quickly by expanding the market.